Importance of readers for junior classes from an education aims standpoint - Milovanović Boško Lj. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2014)
This paper deals with the role of the reader as a coursebook in the education of junior classes pupils in elementary schools. A special attention is given to the reader structure from a methodological point of view, as the role of the reader is not only in providing information but also to develop and nourish other aspects of emotional and intellectual properties of pupils. By reducing a reader to a source of information only, we would reduce its role in education of pupils. It is wrong to equalize the nucleus (core) of a reader with information.